A green printing process for environmentally friendly packaging boxes
The green printing process enhances water-based printing inks by using 3-methacryloyl dopamine and L-lysine pretreatment, boric acid cross-linking, and modified fillers to address the limitations of polyurethane binders, achieving improved water and solvent resistance and abrasion resistance for environmentally friendly packaging boxes.
Patent Information
- Application Number
- CN202310689841.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-12
AI Technical Summary
Water-based printing inks using polyurethane as a binder suffer from low water resistance, solvent resistance, and poor wear and scratch resistance due to insufficient cross-linking density and linear structure, limiting their application in green printing technology.
A green printing process involving the use of 3-methacryloyl dopamine and L-lysine to form a pretreatment solution, combined with a cross-linking solution containing boric acid and a photoinitiator, and the incorporation of modified graphene oxide and titanium dioxide as fillers, along with a polyurethane emulsion enhanced by epoxy acrylate and chain extension processes, to create a water-based printing ink with improved cross-linking properties.
The process results in a water-based printing ink with enhanced water resistance, solvent resistance, and abrasion resistance, ensuring higher printing quality and reduced ink absorption, thereby improving the scope of application in environmentally friendly packaging boxes.
Smart Images

Figure BDA0004279737640000071 
Figure BDA0004279737640000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing ink, in particular to a green printing process for an environmentally friendly packaging box. Background Art
[0002] With the vigorous promotion of green development and the deepening of environmental protection concepts, more and more companies are incorporating environmentally friendly design and printing processes into product packaging. Among them, in the green printing process, traditional solvent-based printing inks are gradually replaced by water-based printing inks. Water-based printing inks can effectively reduce VOCs emissions, reduce the emission of harmful substances, and reduce the impact on the natural environment.
[0003] Water-based printing ink is an ink with certain fluidity and viscosity composed of pigment, binder and related additives in a certain ratio. Among them, the binder, as a material connecting the pigment and the printing substrate, plays an important role in water-based printing ink. Among the prior art, polyurethane is one of the common binders. The water-based ink using it as a binder has the advantages of simplicity, stable performance, safety and environmental protection, and good film formation. However, since most of them are prepared by self-emulsification, they cannot reach the cross-linking density that can be achieved by solvent-based polyurethane, resulting in low water resistance and solvent resistance of this type of ink. At the same time, most polyurethanes are linear, which makes the wear resistance and scratch resistance of water-based printing inks poor, thereby reducing the scope of application.
[0004] In summary, solving the above problems and preparing a printing ink with water-based polyurethane as a binder is of great value for use in green printing technology. Summary of the invention
[0005] The object of the present invention is to provide a green printing process for an environmentally friendly packaging box to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A green printing process for an environmentally friendly packaging box comprises the following steps:
[0008] Step 1: (1) dispersing 3-methacryloyl dopamine and L-lysine in a Tri-buffered solution in sequence to obtain a pretreatment solution having a concentration of 3 to 5 wt %; (2) dispersing boric acid and a photoinitiator in deionized water in sequence to obtain a crosslinking solution;
[0009] Step 2: (1) adding graphene oxide and titanium dioxide to the pretreatment liquid respectively, stirring, centrifugally freeze-drying, obtaining modified graphene oxide and modified titanium dioxide, and mixing the two in proportion to obtain a modified filler; (2) mixing and homogenizing polyurethane emulsion, epoxy acrylate, pigment, deionized water, modified filler, cross-linking liquid, leveling agent, dispersant, and defoaming agent to obtain a water-based printing ink;
[0010] Step 3: (1) spraying the pretreatment liquid on the packaging and surface, and drying; then spraying the crosslinking liquid, drying in the dark, to obtain a pretreated packaging box; (2) printing ink on the surface of the pretreated packaging box, irradiating with ultraviolet light, drying and curing, to obtain an environmentally friendly packaging box.
[0011] More optimally, the raw materials of the water-based printing ink include the following components: by weight, 55 to 65 parts of polyurethane emulsion, 2 to 6 parts of epoxy acrylate, 10 to 15 parts of pigment, 20 to 25 parts of deionized water, 1.5 to 2.5 parts of modified filler, 1 to 1.4 parts of cross-linking liquid, 0.2 to 0.8 parts of leveling agent, 0.5 to 1 parts of dispersant, and 0.5 to 0.8 parts of defoaming agent.
[0012] More optimally, the preparation method of the polyurethane emulsion comprises the following steps: under a nitrogen atmosphere, diisocyanate and polycarbonate diol are added to acetone in sequence, the temperature is raised to 40-55°C, and the reaction is carried out for 30-60 minutes; an organic tin catalyst is added, the temperature is raised to 80-85°C, and the reaction is carried out for 1.5-2.5 hours; an internal emulsifier is added, and the reaction is continued for 2-3 hours; the temperature is lowered to 70-75°C, 1-thioglycerol is added, and the chain is extended for a first time for 40-60 minutes; the temperature is lowered to 30-35°C, 3-acrylamide dopamine and a photoinitiator are added, and the photoclick reaction is carried out for 30-40 minutes; the temperature is raised to 70-75°C, protected from light, epoxy acrylate is added, and the chain is extended for a second time for 30-40 minutes; the temperature is lowered to 30-35°C, triethylamine is added for neutralization, and deionized water is added for emulsification to obtain a polyurethane emulsion with a solid content of 35-42wt%.
[0013] More optimally, the polyurethane emulsion comprises the following raw materials: by weight, 42 to 45 parts of diisocyanate, 95 to 105 parts of polycarbonate diol, 0.05 to 0.1 parts of organic tin catalyst, 7 to 9 parts of internal emulsifier, 3 to 4 parts of 1-thioglycerol, 6 to 7 parts of 3-acrylamidopamine, and 6 to 8 parts of epoxy acrylate.
[0014] More optimally, the spraying amount of the pretreatment liquid is 15-20 g / m2, and the spraying amount of the cross-linking liquid is 0.6-0.9 g / m2.
[0015] More optimally, in the pretreatment solution, the mass ratio of 3-methacryloyldopamine to L-lysine is 1:(1.4-1.5).
[0016] More optimally, the cross-linking solution includes the following raw materials: by weight, 2.5-2.8 parts of boric acid, 0.1-0.12 parts of photoinitiator, and 100 parts of deionized water.
[0017] More optimally, the mass ratio of modified graphene oxide to modified titanium dioxide is (1.5-2):1.
[0018] More optimally, during the ultraviolet irradiation process, the power of the ultraviolet lamp is 1800-2200W, the lamp distance is 8-12cm, the time is 30-60 seconds; the drying and curing temperature is 70-90°C, and the time is 2-4 hours.
[0019] More optimally, an environmentally friendly packaging box is prepared using a green printing process.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) In the scheme, the pretreatment liquid is used to treat the surface of the packaging box. First, the pretreatment liquid can fill the pores on the surface of the packaging box, forming a certain barrier to water on the surface of the packaging box, reducing the absorption of the water-based ink during the printing process of the packaging box, while ensuring the printing quality, reducing the amount of ink used and reducing costs (because too much permeability and absorption will cause the print to be dull, produce see-through or powdering). On the other hand, it can serve as a connecting layer, and with the help of the cross-linking liquid, promote the film formation and cross-linking of the water-based ink, improve the printability, and produce higher printing quality.
[0022] Among them, the pretreatment liquid includes 3-methacryloyl dopamine and L-lysine, which can self-polymerize into a film and be effectively loaded on the surface of the packaging film; on the other hand, it can use the cross-linking property of boric acid and 3-methacryloyl dopamine in the pretreatment layer and the dihydroxyl group contained in the polyurethane in the water-based printing ink to produce strong hydrogen bonding under the promotion of boric acid and photoinitiator in the cross-linking liquid, thereby promoting the formation of a hydrogen bond network between layers and increasing the adhesion of the ink. On the other hand, the unsaturated groups of 3-methacryloyl dopamine can initiate cross-linking with the unsaturated groups in the polyurethane under the action of the photoinitiator, thereby forming a photo-cross-linking network, further increasing the adhesion of the ink.
[0023] In scheme (2), a polyurethane emulsion is prepared, and an aqueous printing ink is prepared with the aid of epoxy acrylate and a modified filler. Compared with the common aqueous ink with aqueous polyurethane as a binder, the aqueous printing ink in this scheme has better improved water resistance, solvent resistance and abrasion resistance.
[0024] Among them, the polyurethane in the polyurethane emulsion uses polycarbonate diol as the main base chain, which makes the polyurethane have good drying and curing properties and resistance to boiling. At the same time, the preparation of polyurethane undergoes two chain extension processes. The first one uses 1-thioglycerol for chain extension, introduces thiol, and uses the click reaction between thiol and olefin to graft 3-acrylamide dopamine, so that the branched chain contains phthalic dihydroxy structure; the second one uses epoxy acrylate for chain extension, so that the polyurethane contains unsaturated groups and can produce ultraviolet light crosslinking. The phthalic dihydroxy structure and unsaturated groups contain additional crosslinking networks, thereby making up for the gap in insufficient crosslinking degree in solvent-based polyurethane inks and enhancing water resistance and solvent resistance.
[0025] Among them, the benzene ring in epoxy acrylate can increase the rigidity of the cross-linked network, thereby increasing the wear resistance and scratch resistance of the ink. In addition, the scheme introduces it into the polyurethane chain break and also introduces it into the water-based printing ink, which enhances the cross-linking degree of the ink and improves the water resistance and solvent resistance.
[0026] Among them, a modified filler is also introduced, which is obtained by modifying graphene oxide and titanium oxide through the self-polymerization of the pretreatment liquid. By introducing the modified filler, the wear resistance and solvent resistance of the pigment are improved. The treatment liquid can not only increase the dispersibility, but also promote the formation of a hydrogen bond network between the modified filler and polyurethane under the action of boric acid, thereby improving the printing performance. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following examples, the CAS number of 3-methacryloyl dopamine is 471915-89-6; the CAS number of L-lysine is 56-87-1; the pH of the Tri-buffer solution is 8.5; the CAS number of 2-hydroxy-2-methylpropiophenone is 7473-98-5; the CAS number of boric acid is 10043-35-3; the CAS number of isophorone diisocyanate is 4098-71-9; the CAS number of dibutyltin dilaurate is 77-58-7; the CAS number of 2,2-dihydroxymethylpropionic acid is 4767-03-7; the CAS number of 3-propylene is 1,1-diol-1-ol is 1,1-diol-2-ol is 1,1-diol-3-ol is 1,1-diol-4-ol is 1,1-diol-5-ol is 1,1-diol-6-ol is 1,1-diol-7-ol is 1,1-diol-8-ol is 1,1-diol-1-ol is 1,1-diol-2-ol is 1,1-diol-3-ol is 1,1-diol-4-ol is 1,1-diol-5-ol is 1,1-diol-6-ol is 1,1-diol-7-ol is 1,1-diol-3-ol is 1 The CAS number of amidodopamine is 471915-89-6, and the CAS number of 1-thioglycerol is 96-27-5; the product number of graphene oxide is NA, provided by Zhejiang Yamei Nanotechnology Co., Ltd.; the product number of titanium dioxide is 2308, provided by Jinan Century Tongda Chemical Co., Ltd.; the CAS number of epoxy acrylate is 71281-65-7, and its hydroxyl value is about 200 mgKOH / g, provided by Nanxiong Sanben Chemical Technology Co., Ltd.; the average molecular weight of polycarbonate diol is 2000 g / mol, provided by Zhengzhou Alpha Chemical Co., Ltd.
[0029] Example 1: Step 1: (1) 3-methacryloyl dopamine and L-lysine in a mass ratio of 1:1.5 are sequentially added to a Tri-buffer solution to obtain a pretreatment solution with a concentration of 4.5 wt%; (2) 2.6 g of boric acid is dispersed in 100 g of deionized water, and 0.1 g of 2-hydroxy-2-methylpropiophenone is added and dispersed uniformly to obtain a cross-linking solution;
[0030] Step 2: (1) adding 5 g of graphene oxide to 100 g of pretreatment solution, stirring for 24 hours, and centrifugally freeze-drying to obtain modified graphene; adding 3 g of titanium dioxide to 100 g of pretreatment solution, stirring for 24 hours, and centrifugally freeze-drying to obtain modified titanium dioxide; mixing and grinding 3 g of modified graphene and 2 g of modified titanium dioxide to obtain a modified filler;
[0031] (2) Under a nitrogen atmosphere, 44 g of isophorone diisocyanate and 100 g of polycarbonate diol were added to acetone in sequence, the temperature was raised to 50° C., and the reaction was carried out for 40 minutes; 0.08 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the reaction was carried out for 2 hours; 8 g of 2,2-dimethylolpropionic acid was added, and the reaction was continued for 2 hours; the temperature was lowered to 70° C., 3.5 g of 1-thioglycerol was added, and the chain was extended for 40 minutes, the temperature was lowered to 35° C., 6.5 g of 3-acrylamidopamine and 0.01 g of 2,2-dimethylolpropionic acid were added, and the mixture was stirred for 30 minutes under 365 nm ultraviolet light; the temperature was raised to 70° C., protected from light, 7 g of epoxy acrylate was added, the chain was extended for 30 minutes, the temperature was lowered to 35° C., triethylamine was added for neutralization, acetone was removed under reduced pressure at 50° C., deionized water was added, and the mixture was stirred and emulsified to obtain a polyurethane emulsion with a solid content of 40%;
[0032] (3) 60 g of polyurethane emulsion, 4 g of epoxy acrylate, 12 g of Lithol Red, 20 g of deionized water, 2 g of modified filler, 1.2 g of cross-linking liquid, 0.5 g of leveling agent TEG410, 0.8 g of dispersant BYK190, and 0.5 parts of defoamer BYK028 were mixed, and ground and homogenized to a fineness of less than 800 mesh to obtain a water-based printing ink;
[0033] Step 3: (1) Spray the pretreatment liquid on the surface of the packaging box at a spraying amount of 20g / m 2 , dried at 80℃; then spray the cross-linking liquid, the spraying amount is 0.8g / m 2 , drying at 80°C in a dark environment to obtain a pre-treated packaging box;
[0034] (2) The pretreated packaging paper was transferred to a printing device equipped with an RX300-1 type UV lamp, and the printing ink and UV light were set to: UV lamp power 2000 W, lamp distance 10 cm, curing time 40 seconds, and drying at 80° C. for 3 hours to obtain an environmentally friendly packaging box.
[0035] Example 2: Step 1: (1) 3-methacryloyl dopamine and L-lysine in a mass ratio of 1:1.5 are sequentially added to a Tri-buffer solution to obtain a pretreatment solution with a concentration of 4.5 wt%; (2) 2.6 g of boric acid is dispersed in 100 g of deionized water, and 0.1 g of 2-hydroxy-2-methylpropiophenone is added and dispersed uniformly to obtain a cross-linking solution;
[0036] Step 2: (1) adding 5 g of graphene oxide to 100 g of pretreatment solution, stirring for 24 hours, and centrifugally freeze-drying to obtain modified graphene; adding 3 g of titanium dioxide to 100 g of pretreatment solution, stirring for 24 hours, and centrifugally freeze-drying to obtain modified titanium dioxide; mixing and grinding 3 g of modified graphene and 2 g of modified titanium dioxide to obtain a modified filler;
[0037] (2) Under a nitrogen atmosphere, 44 g of isophorone diisocyanate and 100 g of polycarbonate diol were added to acetone in sequence, the temperature was raised to 50° C., and the reaction was carried out for 40 minutes; 0.08 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the reaction was carried out for 2 hours; 8 g of 2,2-dimethylolpropionic acid was added, and the reaction was continued for 2 hours; the temperature was lowered to 70° C., 3.5 g of 1-thioglycerol was added, and the chain was extended for 40 minutes, the temperature was lowered to 35° C., 6.5 g of 3-acrylamidopamine and 0.01 g of 2,2-dimethylolpropionic acid were added, and the mixture was stirred for 30 minutes under 365 nm ultraviolet light; the temperature was raised to 70° C., protected from light, 7 g of epoxy acrylate was added, the chain was extended for 30 minutes, the temperature was lowered to 35° C., triethylamine was added for neutralization, acetone was removed under reduced pressure at 50° C., deionized water was added, and the mixture was stirred and emulsified to obtain a polyurethane emulsion with a solid content of 40%;
[0038] (3) 55 g of polyurethane emulsion, 6 g of epoxy acrylate, 10 g of Lithol Red, 20 g of deionized water, 1.5 g of modified filler, 1 g of cross-linking liquid, 0.2 g of leveling agent TEG410, 0.5 g of dispersant BYK190, and 0.8 parts of defoaming agent BYK028 were mixed, and ground and homogenized to a fineness of less than 800 mesh to obtain a water-based printing ink;
[0039] Step 3: (1) Spray the pretreatment liquid on the surface of the packaging box at a spraying amount of 15g / m 2 , dried at 80℃; then spray the cross-linking liquid, the spraying amount is 0.6g / m 2 , drying at 80°C in a dark environment to obtain a pre-treated packaging box;
[0040] (2) The pretreated packaging paper is transferred to a printing device equipped with an RX300-1 type UV lamp, and the printing ink and UV light are set to: UV lamp power 2000W, lamp distance 10cm, curing time 40 seconds, and drying at 80°C for 3 hours to obtain an environmentally friendly packaging box.
[0041] Example 3: Step 1: (1) 3-methacryloyl dopamine and L-lysine in a mass ratio of 1:1.5 are sequentially added to a Tri-buffer solution to obtain a pretreatment solution with a concentration of 4.5 wt%; (2) 2.6 g of boric acid is dispersed in 100 g of deionized water, and 0.1 g of 2-hydroxy-2-methylpropiophenone is added and dispersed evenly to obtain a cross-linking solution;
[0042] Step 2: (1) adding 5 g of graphene oxide to 100 g of pretreatment solution, stirring for 24 hours, and centrifugally freeze-drying to obtain modified graphene; adding 3 g of titanium dioxide to 100 g of pretreatment solution, stirring for 24 hours, and centrifugally freeze-drying to obtain modified titanium dioxide; mixing and grinding 3 g of modified graphene and 2 g of modified titanium dioxide to obtain a modified filler;
[0043] (2) Under a nitrogen atmosphere, 44 g of isophorone diisocyanate and 100 g of polycarbonate diol were added to acetone in sequence, the temperature was raised to 50° C., and the reaction was carried out for 40 minutes; 0.08 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the reaction was carried out for 2 hours; 8 g of 2,2-dimethylolpropionic acid was added, and the reaction was continued for 2 hours; the temperature was lowered to 70° C., 3.5 g of 1-thioglycerol was added, and the chain was extended for 40 minutes, the temperature was lowered to 35° C., 6.5 g of 3-acrylamidopamine and 0.01 g of 2,2-dimethylolpropionic acid were added, and the mixture was stirred for 30 minutes under 365 nm ultraviolet light; the temperature was raised to 70° C., protected from light, 7 g of epoxy acrylate was added, the chain was extended for 30 minutes, the temperature was lowered to 35° C., triethylamine was added for neutralization, acetone was removed under reduced pressure at 50° C., deionized water was added, and the mixture was stirred and emulsified to obtain a polyurethane emulsion with a solid content of 40%;
[0044] (3) 65 g of polyurethane emulsion, 2 g of epoxy acrylate, 15 g of Lithol Red, 25 g of deionized water, 2.5 g of modified filler, 1.4 g of cross-linking liquid, 0.8 g of leveling agent TEG410, 1 g of dispersant BYK190, and 0.8 parts of defoaming agent BYK028 were mixed, and ground and homogenized to a fineness of less than 800 mesh to obtain a water-based printing ink;
[0045] Step 3: (1) Spray the pretreatment liquid on the surface of the packaging box at a spraying amount of 20g / m 2 , dried at 80℃; then spray the cross-linking liquid, the spraying amount is 0.9g / m 2 , drying at 80°C in a dark environment to obtain a pre-treated packaging box;
[0046] (2) The pretreated packaging paper is transferred to a printing device equipped with an RX300-1 type UV lamp, and the printing ink and UV light are set to: UV lamp power 2000W, lamp distance 10cm, curing time 40 seconds, and drying at 80°C for 3 hours to obtain an environmentally friendly packaging box.
[0047] Comparative Example 1: Use purchased 30wt% polyurethane emulsion, item number 2200, provided by Dongguan Zhangmutou Hongji Plastics Trading Company.
[0048] Comparative Example 2: The polyurethane was chain extended only once, and the rest was the same as Example 1; the specific modified steps were as follows:
[0049] Step 2: (2) Under a nitrogen atmosphere, 44 g of isophorone diisocyanate and 100 g of polycarbonate diol are added to acetone in sequence, the temperature is raised to 50° C., and the reaction is carried out for 40 minutes; 0.08 g of dibutyltin dilaurate is added, the temperature is raised to 80° C. and the reaction is carried out for 2 hours; 8 g of 2,2-dihydroxymethylpropionic acid is added, and the reaction is continued for 2 hours; the temperature is lowered to 70° C., 3.5 g of 1-thioglycerol is added, and the chain is extended for 40 minutes at a time, the temperature is lowered to 35° C., 6.5 g of 3-acrylamidopamine and 0.01 g of 2,2-dihydroxymethylpropionic acid are added, and the mixture is stirred for 30 minutes under 365 nm ultraviolet light; triethylamine is added for neutralization, acetone is removed under reduced pressure at 50° C., deionized water is added, stirred and emulsified, and a polyurethane emulsion with a solid content of 40% is obtained.
[0050] Comparative Example 3: Polyurethane is chain extended only twice, and the rest is the same as Example 1; the specific modified steps are as follows:
[0051] Step 2: (2) Under a nitrogen atmosphere, 44 g of isophorone diisocyanate and 100 g of polycarbonate diol are added to acetone in sequence, the temperature is raised to 50° C., and the reaction is carried out for 40 minutes; 0.08 g of dibutyltin dilaurate is added, the temperature is raised to 80° C., and the reaction is carried out for 2 hours; 8 g of 2,2-dihydroxymethylpropionic acid is added, and the reaction is continued for 2 hours; the temperature is lowered to 70° C., 7 g of epoxy acrylate is added, and the chain is extended for 40 minutes, the temperature is lowered to 35° C., triethylamine is added for neutralization, acetone is removed under reduced pressure at 50° C., deionized water is added, stirred and emulsified, and a polyurethane emulsion with a solid content of 40% is obtained.
[0052] Comparative Example 4: Epoxy acrylate is not introduced, and the rest is the same as Example 1; the specific modification steps are as follows:
[0053] Step 2: (3) Mix 60 g of polyurethane emulsion, 12 g of Lithol Red, 20 g of deionized water, 2 g of modified filler, 1.2 g of cross-linking liquid, 0.5 g of leveling agent TEG410, 0.8 g of dispersant BYK190, and 0.5 parts of defoaming agent BYK028, and grind and homogenize to a fineness of less than 800 mesh to obtain a water-based printing ink.
[0054] Comparative Example 5: Only modified graphene was introduced, and the rest was the same as Example 1; the specific modification steps were as follows:
[0055] Step 2: (1) Add 5 g of graphene oxide to 100 g of pretreatment solution, stir for 24 hours, centrifuge and freeze-dry to obtain modified graphene, and use it as a modified filler.
[0056] Experimental comparison test: (1) Take the printed environmentally friendly packaging box, and test the adhesion by the cross-cut method. Use a cross-cutting instrument to divide it into multiple small grids, use 3M pressure-sensitive adhesive to stick on the grids, and quickly tear it off. Then look at the peeling book to determine the adhesion level. The peeling area of level 0 is 0%, the peeling area of level 1 is 0-5%, the peeling area of level 2 is 5-15%, the peeling area of level 3 is 15-35%, the peeling area of level 4 is 35-65, and the peeling area of level 5 is >65%. (2) Take the printed environmentally friendly packaging box, use a rubber wheel with a load of 750g, rotate at a speed of 60r / min, rub for 10 minutes, weigh the weight before and after, and obtain the wear amount. (3) Take the printed environmentally friendly packaging box, stack 12 clean filter papers on it, press it with a glass plate, immerse it in deionized water for 96 hours, take it out, and observe the staining of the filter paper; immerse it in a 50% ethanol aqueous solution in the same way for 96 hours, test the solvent resistance, take it out, and observe the staining of the filter paper. The obtained data are shown in the following table:
[0057]
[0058]
[0059] It can be seen from the data in the above table that the water-based printing ink prepared in the scheme has good printability. After printing through the printing process, the obtained ink film has excellent adhesion, water resistance, solvent resistance and wear resistance. Comparing the data of Example 1 with Comparative Examples 1 to 5, it can be seen that the use of commercially available polyurethane emulsion in Comparative Example 1 reduces water resistance, solvent resistance and wear resistance. In Comparative Example 2 and Comparative Example 3, only a single chain extension is performed, which reduces the crosslinking of the branched chains, thereby reducing the degree of crosslinking and the performance. In Comparative Example 4, since epoxy acrylate is not introduced, the degree of crosslinking is reduced, which reduces the performance; in Comparative Example 5, due to the single introduction of modified graphene, the wear resistance is reduced. At the same time, due to nano-titanium dioxide, ultraviolet light crosslinking can be promoted, so the other properties are slightly reduced.
[0060] Experimental basic test: The water-based printing ink prepared in Example 1 was subjected to relevant performance tests: (1) Referring to GB / T13217.4, a digital viscosity tester was used to measure the viscosity at room temperature with a 60# rotor; the drying speed was tested according to the initial drying method of GB / T13217.4; the water-based printing ink was placed in an oven at 60°C, taken out after 4 hours, cooled naturally, and the sedimentation was tested.
[0061] Results: The viscosity was 27.3s, the initial dryness was 13mm / 30s, and there was no precipitation at the bottom, indicating good printability.
[0062] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An environmentally friendly packaging box using green printing technology, Features: The following steps are involved: Step 1: (1) dispersing 3-methacryloyl dopamine and L-lysine in a Tris-buffered solution in sequence to obtain a pretreatment solution with a concentration of 3 to 5 wt %; (2) dispersing boric acid and a photoinitiator in deionized water in sequence to obtain a crosslinking solution; Step 2: (1) adding graphene oxide and titanium dioxide to the pretreatment liquid respectively, stirring, centrifugally freeze-drying, obtaining modified graphene oxide and modified titanium dioxide, and mixing the two in proportion to obtain a modified filler; (2) mixing and homogenizing polyurethane emulsion, epoxy acrylate, pigment, deionized water, modified filler, cross-linking liquid, leveling agent, dispersant, and defoaming agent to obtain a water-based printing ink; Step 3: (1) spraying the pretreatment liquid on the package and surface and drying; Then spray the cross-linking liquid, dry in the dark, and obtain a pre-treated packaging box; (2) printing ink on the surface of the pretreated packaging box, irradiating with ultraviolet light, drying and curing, and obtaining an environmentally friendly packaging box; The preparation method of the polyurethane emulsion comprises the following steps: in a nitrogen atmosphere, adding diisocyanate and polycarbonate diol to acetone in sequence, heating to 40-55° C., and reacting for 30-60 minutes; adding an organic tin catalyst, heating to 80-85° C., and reacting for 1.5-2.5 hours; adding an internal emulsifier, and continuing the reaction for 2-3 hours; cooling to 70-75° C., adding 1-thioglycerol, and performing a primary chain extension for 40-60 minutes; cooling to 30-35° C., adding 3-acrylamide dopamine and a photoinitiator, and performing a photoclick reaction for 30-40 minutes; heating to 70-75° C., protecting from light, adding epoxy acrylate, and performing a secondary chain extension for 30-40 minutes; cooling to 30-35° C., adding triethylamine for neutralization, and adding deionized water for emulsification to obtain a polyurethane emulsion with a solid content of 35-42wt%.
2. According to claim 1, a green printing process for an environmentally friendly packaging box, Features: The raw materials of the water-based printing ink include the following components: by weight, 55 to 65 parts of polyurethane emulsion, 2 to 6 parts of epoxy acrylate, 10 to 15 parts of pigment, 20 to 25 parts of deionized water, 1.5 to 2.5 parts of modified filler, 1 to 1.4 parts of cross-linking liquid, 0.2 to 0.8 parts of leveling agent, 0.5 to 1 parts of dispersant, and 0.5 to 0.8 parts of defoaming agent.
3. According to claim 1, a green printing process for an environmentally friendly packaging box, Features: The polyurethane emulsion comprises the following raw materials: by weight, 42-45 parts of diisocyanate, 95-105 parts of polycarbonate diol, 0.05-0.1 parts of organic tin catalyst, 7-9 parts of internal emulsifier, 3-4 parts of 1-thioglycerol, 6-7 parts of 3-acrylamide dopamine, and 6-8 parts of epoxy acrylate.
4. The green printing process for an environmentally friendly packaging box according to claim 1, Features: The spraying amount of the pretreatment liquid is 15-20 g / m 2 The spraying amount of the cross-linking liquid is 0.6 to 0.9 g / m 2 .
5. The green printing process for an environmentally friendly packaging box according to claim 1, Features: In the pretreatment solution, the mass ratio of 3-methacryloyl dopamine to L-lysine is 1:(1.4-1.5).
6. The green printing process for an environmentally friendly packaging box according to claim 1, Features: The cross-linking solution comprises the following raw materials: by weight, 2.5 to 2.8 parts of boric acid, 0.1 to 0.12 parts of a photoinitiator, and 100 parts of deionized water.
7. The green printing process for an environmentally friendly packaging box according to claim 1, Features: The mass ratio of modified graphene oxide to modified titanium dioxide is (1.5-2):
1.
8. The green printing process for an environmentally friendly packaging box according to claim 1, Features: During the ultraviolet irradiation process, the power of the ultraviolet lamp is 1800-2200W, the lamp distance is 8-12cm, the time is 30-60 seconds; the drying and curing temperature is 70-90°C, and the time is 2-4 hours.
9. An environmentally friendly packaging box according to any one of claims 1 to 8, prepared by a green printing process.
Citation Information
Patent Citations
Waterborne polyurethane / dopamine modified graphene nano-composite emulsion preparation method
CN107828046A
Environment-friendly printed UV oil ink for packaging material and preparation method thereof
CN108587307A
Water-resistant paper plastic composite material and preparation method thereof
CN110373938A
Printed thermoplastic resin products and method for printing such products
EP0588533A2
Polyurethane resins, process for producing the same, and uses thereof
US5656701A
